2020
DOI: 10.29278/azd.720106
|View full text |Cite
|
Sign up to set email alerts
|

Çarşamba Ekolojik Koşullarında Yetiştirilen Bazı Standart Elma Çeşitlerinin Verim ve Meyve Özellikleri

Abstract: Çalışma, Çarşamba (Samsun) ilçesinde M9 anacı üzerine aşılı üç elma çeşidinin (Granny Smith, Royal Gala ve Galaxy Gala) verim ve meyve özelliklerini belirlemek amacıyla 2015 ve 2016 yıllarında 5 ve 6 yaşlı ağaçlarda yürütülmüştür. İncelenen elma çeşitlerinde ağaç başına verim 11.30 kg (Granny Smith)-18.91 kg (Galaxy Gala); verim etkinliği 1.69 kg cm -2 (Granny Smith)-3.43 kg cm -2 (Galaxy Gala) arasında tespit edilmiştir. Meyve özelliklerden; meyve ağırlığı 165.23 g (Royal Gala)-187.87 g (Granny Smith), meyve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In the study conducted by Karşı and Aslantaş [40], the TSS content varied between 7.73% (Hüryemez) and 14.60% (Golden Delicious). In another study, they noted that the content of TSS ranged from 10.24% (Granny Smith) to 12.07% (Royal Gala) [41]. Boyacı et al [38] conducted to determine the biochemical content of apple fruits, they determined the pH value as 4.03 in Red Chief variety and 3.31 in Granny Smith variety.…”
Section: Ssc Ph Acidity and Pomological Propertiesmentioning
confidence: 99%
“…In the study conducted by Karşı and Aslantaş [40], the TSS content varied between 7.73% (Hüryemez) and 14.60% (Golden Delicious). In another study, they noted that the content of TSS ranged from 10.24% (Granny Smith) to 12.07% (Royal Gala) [41]. Boyacı et al [38] conducted to determine the biochemical content of apple fruits, they determined the pH value as 4.03 in Red Chief variety and 3.31 in Granny Smith variety.…”
Section: Ssc Ph Acidity and Pomological Propertiesmentioning
confidence: 99%
“…The antioxidant activity analysis results of pear genotypes also revealed that it ranged between 208 mg/1000 g TEAC and 1454 mg/1000 g TEAC in 2020; whereas, it remained between 275 mg/1000 g TEAC and 1201 mg/1000 g TEAC in 2021 (Tables 3, 4, and 5, Figures 1, 2, 3, and 4). Considering the previous studies conducted in Türkiye, the weight of pear species grown in Ünye district of Ordu province in 2012 was between 18.7 g and 258.3 g (Bostan and Acar, 2012) in Gürgentepe district of Ordu province, and the phenological, morphological and pomological characteristics of the local pear species grown in these districts were observed. A study conducted to identify some fruit characteristics of early pear (Pyrus communis L.) types grown in the Eğirdir district reported that the fruit weight ranged between 36.23 g and 146.65 g (Kılıç, 2015).…”
Section: Resultsmentioning
confidence: 88%
“…In terms of fruit firmness, the highest values were obtained from Granny Smith/M9, Granny Smith/MM 106, and Fuji/MM 106 cultivars. In a study carried out in Çarşamba (Samsun) ecological conditions, it was reported that the highest fruit weight and firmness were obtained from the Granny Smith cultivar as 187.7 g and 86.11 N, respectively (Balta et al, 2020). Oztürk et al (2016), in their study conducted in Ordu province, reported the fruit weight was between 136.2 (Red Chief)-207.1 g, and the fruit firmness was between 63.43 (Mondial Gala)-82.83 N (Red Chief).…”
Section: Resultsmentioning
confidence: 99%
“…The differences between the cultivars in fruit size values were found to be statistically significant (p<0.05). In previous studies, the dimensional fruit characteristics have been reported; in the study carried out in Niğde conditions, fruit width was 70.09 (Galaxy Gala/M9)-75.86 mm (Granny Smith/M9), fruit length was 57.55 (Mondial Gala/M9)-66.68 mm (Granny Smith/M9) Ceylan (2008); in a study conducted in Ordu province, fruit width was 67.41 (Red Chief) -77.60 mm (Granny Smith), fruit length was 58.65 (Red Chief) -69.07 mm (Granny Smith) (Öztürk et al, 2016); in Çarşamba region, fruit width was 70.74 (Royal Gala)-74.34 mm (Granny Smith), fruit width was 72.67 (Royal Gala)-76.91 mm (Granny Smith) and fruit length was 62.29 (Royal Gala)-65.90 mm (Granny Smith) (Balta et al, 2020). It has been observed that the cultivars examined in terms of fruit weight have relatively higher values than other studies, and they have similarities in fruit firmness and fruit size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation